2018
DOI: 10.3892/ol.2018.8933
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA‑205 is downregulated in hepatocellular carcinoma and inhibits cell growth and metastasis via directly targeting vascular endothelial growth factor A

Abstract: MicroRNAs (miRs) are an emerging class of non-coding, endogenous and small RNA molecules that serve important functions in tumorigenesis and development. The present study investigated the expression, functions and molecular mechanism underlying miR-205 in hepatocellular carcinoma. miR-205 was downregulated in hepatocellular carcinoma tissues and cell lines. Ectopic miR-205 expression suppressed hepatocellular carcinoma cell proliferation, migration and invasion . In addition, vascular endothelial growth facto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
13
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 39 publications
3
13
0
Order By: Relevance
“…VEGFA mRNA expression levels negatively correlated with miR‐205‐5p expression, highlighting the transcriptional regulation of VEGFA mRNA by this miRNA. Previous studies have already identified the regulation of VEGFA by miR‐205‐5p . Additionally, the results reported here indicate that the VEGFA/miR‐205‐5p correlation might be regulated by OS in ARPE‐19 cells.…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…VEGFA mRNA expression levels negatively correlated with miR‐205‐5p expression, highlighting the transcriptional regulation of VEGFA mRNA by this miRNA. Previous studies have already identified the regulation of VEGFA by miR‐205‐5p . Additionally, the results reported here indicate that the VEGFA/miR‐205‐5p correlation might be regulated by OS in ARPE‐19 cells.…”
Section: Discussionsupporting
confidence: 70%
“…7 In addition, we have identified some potential targets of miR-205-5p and their biological processes. 7,[11][12][13]47 Moreover, it has been suggested that miR-205-5p could interact indirectly via PI3K/AKT also involved in angiogenesis. In fact, it F I G U R E 5 VEGFA-mediated Vasculogenesis is regulated by miR-205-5p.…”
Section: Vegfa Mrna As a Mir-205-5p Targetmentioning
confidence: 99%
See 1 more Smart Citation
“… 21 In addition, miR-205 can suppress the growth and metastasis of hepatic carcinoma cells by targeting vascular endothelial growth factor (VEGF). 22 In our study, SC cells showed weakened proliferation and invasion, intensified apoptosis, elevated caspase-3 and Bax expression, as well as lowered Bcl-2 expression after being transfected with miR-205-mimics, which indicates that miR-205 serves as a tumor suppressor in SC. We explored the association between miR-205 and propofol, finding that inhibition of miR-205 could weaken the effect of propofol on the biological events of SC cells, which suggests that propofol can act as an anticancer agent in SC by regulating miR-205.…”
Section: Discussionsupporting
confidence: 52%
“…As expected from the expression of miR-200 family members, ZEB-1 is barely detected in epithelial cells suggesting that the downregulation of these miRs is an essential early step in tumor metastasis 20 . The EMT program itself is orchestrated by ZEB1 binding to E-boxes in the E-cadherin promoter, repressing its transcription and inciting metastatic outgrowth by causing carcinoma cells to enter a metastasis-initiating cell state 6972 . Restoring miR-21 and miR-205 expression to non-tumorigenic levels by 11PS04 treatment also normalized the transcription and translation of PDCD4, ZEB-1 and E-Cadherin possibly altering the EMT program itself.…”
Section: Discussionmentioning
confidence: 99%